Analisis Kurikulum Tingkat Satuan Pendidikan (KTSP) Pada Mata Pelajaran Sejarah Sebagai Perbandingan Terhadap Implementasi Kurikulum Merdeka (IKM) - Okhaifi Prasetyo; Aulia Rahman (Pendidikan IPS FKIP ULM, 2023)
The curriculum is a strategic basis for the design of education; education in a country must aim to become independent and empower every human being who takes an education. This article examines the education unit-level curriculum (KTSP) in historical subjects. Using the literature study method, researchers conduct research by collecting a number of books, articles, magazines, and other text sources related to the problem and research objectives. The results show that the Education Unit Level Curriculum (KTSP) is a curriculum compiled and implemented by every element of education in Indonesia. The purpose of implementing KTSP is for education units to give authority (autonomy) to each educational institution and to encourage schools to make participatory decisions in developing the curriculum for the sake of self-sufficiency and empowerment of every educational actor, especially in historical subjects. But KTSP is the same as any other curriculum with weaknesses and strengths. These weaknesses include a lack of human resources, minimal infrastructure, a lack of understanding of teachers about KTSP, and a reduction in teaching hours which causes a reduction in teacher income. Then there are also several advantages, namely: encouraging the realization of school autonomy, encouraging the ability of teachers, and allowing schools to arrange their lessons to suit the needs of students.Keywords: Analysis, KTSP, IKM, History Lesson.